2002
DOI: 10.1128/aem.68.6.2754-2762.2002
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Methyl tert -Butyl Ether and Other Fuel Oxygenates by a New Strain, Mycobacterium austroafricanum IFP 2012

Abstract: A strain that efficiently degraded methyl tert-butyl ether (MTBE) was obtained by initial selection on the recalcitrant compound tert-butyl alcohol (TBA). This strain, a gram-positive methylotrophic bacterium identified as Mycobacterium austroafricanum IFP 2012, was also able to degrade tert-amyl methyl ether and tert-amyl alcohol. Ethyl tert-butyl ether was weakly degraded. tert-Butyl formate and 2-hydroxy isobutyrate (HIBA), two intermediates in the MTBE catabolism pathway, were detected during growth on MTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 37 publications
3
90
0
9
Order By: Relevance
“…Johnson and Hyman (2006) recently demonstrated a new capacity of P. putida GPo1 to also grow on the gaseous n-alkanes, propane and butane, confirming the broad alkane spectrum of the alkane hydroxylase in this strain. Among the strains of M. austroafricanum examined in this study, three of them were able to use C 2 to C 16 n-alkanes as their sole carbon and energy source: M. austroafricanum IFP 2012 and IFP 2015, isolated for their capacity to grow on TBA and MTBE (François et al 2002; Lopes Ferreira et al tuberculosis H37Rv alkB (accession numbers: X58890 and Z95121, respectively) and of P. putida GPo1 (accession numbers: AJ249825 and CAB54050, respectively) were included for comparison. The topology of the alkB sequences of mycobacteria was obtained by TopPred prediction (Claros and von Heijne 1994) and compared to the topology of P. Putida GPo1 alkB gene (Van Beilen et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Johnson and Hyman (2006) recently demonstrated a new capacity of P. putida GPo1 to also grow on the gaseous n-alkanes, propane and butane, confirming the broad alkane spectrum of the alkane hydroxylase in this strain. Among the strains of M. austroafricanum examined in this study, three of them were able to use C 2 to C 16 n-alkanes as their sole carbon and energy source: M. austroafricanum IFP 2012 and IFP 2015, isolated for their capacity to grow on TBA and MTBE (François et al 2002; Lopes Ferreira et al tuberculosis H37Rv alkB (accession numbers: X58890 and Z95121, respectively) and of P. putida GPo1 (accession numbers: AJ249825 and CAB54050, respectively) were included for comparison. The topology of the alkB sequences of mycobacteria was obtained by TopPred prediction (Claros and von Heijne 1994) and compared to the topology of P. Putida GPo1 alkB gene (Van Beilen et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a few strains were able to grow on MTBE and therefore on TBA; Methylibium petroleiphilum PM1 (Hanson et al 1999;Nakatsu et al 2006), Hydrogenophaga flava ENV735 (Hatzinger et al 2001), M. austroafricanum IFP 2012 (François et al 2002) and, more recently, M. austroafricanum IFP 2015 (Lopes Ferreira et al 2006b) and Aquincola tertiaricarbonis L10 (Lechner et al 2007). These strains have been studied at the physiological level, but the genes and enzymes involved in the oxidation of MTBE and in the oxidation of TBA are still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, however, several studies have shown that bacterial [1][2][3][4][5][6][7] and fungal [8] isolates are capable of breaking the ether bond of ether fuels, generating tert-butyl alcool (TBA) in the process. TBA can then be further metabolized, either by the same microorganism [2,[5][6][7] or by other microorganisms living in the same natural or artificial consortium [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A Mycobacterium austroafricanum IFP 2012 jelű törzset TBA-bontóként izolálták, de a későbbiekben igazolták, hogy MTBE, TAME és TAA bontására is képes, ETBE-n viszont gyengén nő [112]. Az MTBE lebontási köztitermékei közül a TBF-et, a TBA-t, az MPD-t, a 2-HIBA-t és az acetont azonosították.…”
Section: áBra Az Etbe Metabolikus úTvonala a Rhodococcus Ruber Ifp 20unclassified